2001
DOI: 10.1097/00075198-200110000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Severe infections after bone marrow transplantation

Abstract: Bone marrow transplantation and stem cell transplantation have become standard therapies offering potential cures for a number of hematologic malignancies and immunologic disorders. Severe infection remains a life threatening complication after transplantation, contributes significantly to morbidity, and may necessitate admission to the ICU. It is estimated that between 20 and 40% of patients receiving bone marrow transplant will require ICU admission in the initial posttransplantation phase. Historically, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
0
14
0
4
Order By: Relevance
“…Survival rates may be increasing however since recent data demonstrate hospital and one year survival of 54-60% and 43%, respectively [9,10]. Outcomes after haemopoeitic stem cell transplantation (HSCT) appear to be worse [11], although there have been a number of papers suggesting that the prognosis may have improved even among HSCT recipients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Survival rates may be increasing however since recent data demonstrate hospital and one year survival of 54-60% and 43%, respectively [9,10]. Outcomes after haemopoeitic stem cell transplantation (HSCT) appear to be worse [11], although there have been a number of papers suggesting that the prognosis may have improved even among HSCT recipients [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on risk factors, the incidence of invasive fungal infections (IFI) in allogeneic HSCT recipients ranges from 14% to 25% [3,4]. These infections count among the most dangerous complications in the HSCT setting [5,6] being one of the major causes of respiratory failure in this context. Several studies have indicated a very poor outcome with a very high mortality (above 95%) in HSCT patients with respiratory failure requiring artificial ventilation (AV), especially when combined with hepatic and renal dysfunction [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments in our laboratory using rats with experimental autoimmune MG suggested that complete elimination of the existing immune system and replacement by means of bone marrow transplantation (BMT) could restore the animals to their pristine immunological state, without residual responsiveness to the antigen AChR 7,8 Similar approaches have been tested in a variety of human autoimmune disorders. 9 -13 However, the risks associated with BMT, 14,15 and the fact that the autoimmune disorders recurred in some cases, 16,17 has limited the enthusiasm for these procedures.…”
mentioning
confidence: 99%